2020
DOI: 10.1016/j.jcv.2020.104579
|View full text |Cite
|
Sign up to set email alerts
|

Extraction-free SARS-CoV-2 detection by rapid RT-qPCR universal for all primary respiratory materials

Abstract: Highlights Rapid SARS-CoV-2 detection without RNA extraction. Universal direct RT-qPCR protocol suitable for all respiratory materials. Significant correlation of Ct values between direct and RNA RT-qPCR. High SARS-CoV-2 detection rate by direct RT-qPCR of 95.8 % for Ct values <35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 7 publications
6
67
2
1
Order By: Relevance
“…For samples with Ct < 30, observed sensitivities were similar in all three assays. A previous study assessing PrimeDirect among 91 samples showed higher sensitivity rate than in our study ( Lübke et al, 2020 ). This study showed an overall sensitivity of 84.9% rising to 95.8% among samples with Ct <35 while it is 55.1% and 91.9% among samples with Ct <30 in our study ( Lübke et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 85%
“…For samples with Ct < 30, observed sensitivities were similar in all three assays. A previous study assessing PrimeDirect among 91 samples showed higher sensitivity rate than in our study ( Lübke et al, 2020 ). This study showed an overall sensitivity of 84.9% rising to 95.8% among samples with Ct <35 while it is 55.1% and 91.9% among samples with Ct <30 in our study ( Lübke et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 85%
“…To date, several protocols that effectively inactivate SARS-CoV-2 in clinical and some research settings have been described, including use of heat to ≥95 °C as a part of diagnostic polymerase chain reaction (quantitative PCR) assays performed in clinical specimens [ 7 , 8 , 9 , 10 ], use of heat to 56 °C for 30 min. in serum samples [ 10 ], use of alcohol-based hand sanitizers [ 11 ], use of ultraviolet (UV) light to disinfect surface contamination [ 12 ] use of lysis buffers containing sodium dodecyl sulfate (SDS) or Triton-X100 in cell culture supernatant or nasopharyngeal samples [ 13 , 14 , 15 , 16 ], and use of heat to 80 °C, Trizol ® , detergents and UV energy in stocks of SARS-CoV-2 harvested from infected Vero E6 cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, several studies have already looked into SARS-CoV-2 sample preparation to expedite and simplify the process ( Marais et al, 2020 ; Rabe and Cepko 2020 ; Wozniak et al, 2020 ). In addition, some studies have also examined sample preparation-free assay by utilizing RT-PCR ( Lübke et al, 2020 ) and RT-LAMP ( Wei et al, 2020 ). Future works should focus on developing a fully streamlined process (raw sample-in-answer-out) by seamlessly combining the sample preparation with the CRISPR assay.…”
Section: Summary and Future Perspectivementioning
confidence: 99%